Mismatching and job tasks in Germany - rising over-qualification through polarization? - Rohrbach-Schmidt, Daniela [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2011)
"The paper looks for evidence on whether there is a rise in over-qualification caused by changing skill demand, i.e. a decline of middling jobs, in Germany. We use the BIBB/IAB and BIBB/BAuA Employment Surveys 1979, 1985/86, 1991/92, 1998/1999 and 2005/2006 to compute measures of person-to-job matching. Firstly, we explore their trends over time. Secondly, we analyze whether trends in over-qualification are related to changes in workers’ job tasks. The paper thus contributes to the literature by providing in-depth figures on the incidence of qualification- and skill-based mismatching in Germany within the last three decades. Secondly, we add to the literature by linking the 'task-based approach' to the debate on mismatching in Germany." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2.3 Beschäftigungsformen; Mismatch; Berufliche Qualifikation; Adäquate Beschäftigung; Überqualifikation; Tätigkeitsmerkmal; Erwerbstätiger; Befragung